A Review of Ethnomedicinal Uses, Phytochemistry and Pharmacology of Nigerian Crotons - , Sani M. Isyaka; , Atanda Hameed Akintayo; , Abdullahi M. Abdullahi (Archives of Current Research International, 2024)
Approximately 80% of the world's population relies on traditional plants to produce and synthesize contemporary medications. In the past, the production of plants as sources of pharmaceuticals or medicines for wound healing and treatment was based on superstition and experience that was passed down from one generation to the next. The majority of these plants belong to the families Euphorbiaceae, Leguminoceae, Rutaceae, and Piperaceae. The Euphorbiaceae family includes Croton plants. They are found in tropical and sub-tropical areas of both hemispheres and comprise of 1,300 species of trees, shrubs, and herbs. This work is a critical review of chemical constituents, ethnomedicinal, phytochemistry and pharmacology of various Nigerian Croton species. The term "ethnomedicinal potentials" refers to the therapeutic applications of plants that have positive pharmacological effects on both human and animal bodies. Prior to the development of modern medicine, certain Croton species were used to cure rheumatism, diabetes, diarrhea, cancer, and other illnesses. Active alkaloids are abundant in the Croton genus. In addition to triterpenoids, flavonoids, sesquiterpenoids, phytosterols, N-containing chemicals, cyclohexane derivatives, aliphatic molecules, ferulic acid ester derivatives and diterpenoids are said to be widely distributed throughout the African Crotons.